The role of the Municipal Council for the Defense of the Environment in the elaboration of the Municipal Plan for the Integrated Management of Solid Waste in Araraquara - State of São Paulo - Mattos, Isabella; Orsi, Rafael Alves; Santiago , Cristine Diniz (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Municipalities play a key role in the public policy cycle because they are directly involved in managing their respective territorial areas. When it comes to solid waste in Brazil, one significant way to mitigate its impacts is through public participation in the National Solid Waste Policy, established by Law No. 12.305 of 2010. Municipal plans serve as the planning and implementation documents for this policy. In this context, the municipality of Araraquara was chosen as the case study, given its solid waste management system and its history of progressive municipal governance. This study aimed to understand whether and how institutionalized public participation occurred through the Municipal Council for the Defense of the Environment (COMDEMA) during the formulation of the Municipal Plan for Integrated Solid Waste Management between 2011 and 2021. To achieve this, we conducted a bibliographic review, documentary research, and semi-structured interviews, analyzing the data using Laurence Bardin’s content analysis technique. The results indicate that, although the management instrument explicitly mentions participation, COMDEMA’s input did not effectively translate into decisions by the council regarding the plan formulation during the period analyzed. This was due to the vulnerabilities within the council’s structure, which hinder the inclusion of solid waste issues in meetings for discussion and decision-making. Hopefully, this research will foster further discussions about COMDEMA and its role in solid waste management.